Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.7554/elife.76143
|View full text |Cite
|
Sign up to set email alerts
|

New insights into anatomical connectivity along the anterior–posterior axis of the human hippocampus using in vivo quantitative fibre tracking

Abstract: The hippocampus supports multiple cognitive functions including episodic memory. Recent work has highlighted functional differences along the anterior–posterior axis of the human hippocampus, but the neuroanatomical underpinnings of these differences remain unclear. We leveraged track-density imaging to systematically examine anatomical connectivity between the cortical mantle and the anterior–posterior axis of the in vivo human hippocampus. We first identified the most highly connected cortical areas and deta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 94 publications
(176 reference statements)
6
31
0
Order By: Relevance
“…Once pattern completion is initiated, most information is relayed via the subiculum to the entorhinal cortex which in turn has back-projections to other cortical areas (Chrobak et al, 2000;Rolls, 2013;Staresina & Wimber, 2019). A majority of direct hippocampal and entorhinal efferents terminate in late areas of the visual processing hierarchy where representations cluster in abstract-semantic categories, while there are few connections to low-level sensory areas (Dalton et al, 2022;Insausti & Muñoz, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once pattern completion is initiated, most information is relayed via the subiculum to the entorhinal cortex which in turn has back-projections to other cortical areas (Chrobak et al, 2000;Rolls, 2013;Staresina & Wimber, 2019). A majority of direct hippocampal and entorhinal efferents terminate in late areas of the visual processing hierarchy where representations cluster in abstract-semantic categories, while there are few connections to low-level sensory areas (Dalton et al, 2022;Insausti & Muñoz, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Once pattern completion is initiated, most information is relayed via the subiculum to the entorhinal cortex which in turn has back-projections to other cortical areas (Chrobak et al, 2000; Rolls, 2013; Staresina & Wimber, 2019). A majority of direct hippocampal and entorhinal efferents terminate in late areas of the visual processing hierarchy where representations cluster in abstract-semantic categories, while there are few connections to low-level sensory areas (Dalton et al, 2022; Insausti & Muñoz, 2001). We therefore expect that memories are initially reinstated on a conceptual level, and information coded in lower-level visual areas can only be reached at later stages of memory reconstruction (Insausti & Muñoz, 2001; Linde-Domingo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While the principal anteroposterior gradient is well-established in the literature (Genon et al, 2021; Poppenk et al, 2013), demonstrated not only in function (Przeździk et al, 2019; Tian et al, 2020; vos de Wael et al, 2018), but also in structural covariance (Plachti et al, 2019), gene expression (Vogel et al, 2020), and in graded anteroposterior transitions of anatomical connections (Beaujoin et al, 2018; Dalton et al, 2022), the secondary long-axis gradient remains more elusive. Here, we present multiple lines of evidence supporting an interpretation of the second-order gradient as a local representation of the principal gradient of macroscale cortical organization (Huntenburg et al, 2018; Margulies et al, 2016): the unimodal-transmodal distribution of a) large-scale cortical networks in gradient space (Figure 2); b) meta-analytic terms in Neurosynth (Figure 3B); and the spatial correspondence with a functional unimodal-transmodal cortical gradient (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The human hippocampus is a crucial brain structure responsible for memory processing, learning, spatial navigation and emotions (Chauhan P et al, 2021) and is vulnerable to most neurocognitive diseases (Baazaoui N et al, 2022). Recent researches have shown that the hippocampal longitudinal organization is tightly integrated into large-scale functional/structural networks (Dalton MA et al, 2022;Kharabian Masouleh S et al, 2020; Vogel JW et al, 2020). (Plachti A et al, 2020) discovers different longitudinal structural subdivisions of the hippocampus that relate to normal aging and dementias.…”
Section: Introductionmentioning
confidence: 99%